Neuromagnetic imaging of cortical oscillations accompanying tactile stimulation - Cheyne, Douglas; Gaetz, William; Garnero, Line; Lachaux, Jean-Philippe; Ducorps, Antoine; Schwartz, Denis; Varela, Francisco J. (Brain research. Cognitive brain research, 2003)
We applied a new method of imaging frequency-specific changes in brain activity in humans during a finger brushing task in order to measure changes in cortical rhythms during tactile stimulation. Neuromagnetic recordings were conducted in five subjects using a whole-head MEG system during tactile stimulation of the right index finger, with or without visual feedback, and while viewing another individual’s index finger being stimulated. Volumetric images of changes in source power relative to pre-stimulus baseline levels were computed with 2 mm resolution over the entire brain using a minimum-variance beamforming algorithm (synthetic aperture magnetometry). Onset of tactile stimulation produced a brief (200–300 ms) suppression of mu band (8–15 Hz) and beta band (15–30 Hz) cortical activity in the primary somatosensory and primary motor cortex, respectively, followed by a bilateral increase in beta band activity (‘beta rebound’) in motor cortex. This pattern of suppression/rebound was absent when subjects observed finger brushing or brushing motions without receiving stimulation. In contrast, these conditions resulted in bilateral increases in beta band activity in sensorimotor areas and decreased power in the alpha (8–12 Hz) band in primary visual areas. These results show that spatially filtered MEG provides a useful method for directly imaging the temporal sequence of changes in cortical rhythms during transient tactile stimulation, and provide evidence that observation of tactile input to another individual’s hand, or object motion itself, can influence independent rhythmic activity in visual and sensorimotor cortex.